IMPACT OF PANDEMIC ON TOURISM INDUSTRY OF ASSAM, INDIA- WITH SPECIAL EMPHASIS ON KAZIRANGA NATIONAL PARK AND KAMAKHYA TEMPLE - Koch, Preceileena; Kar, Bimal kumar (Revista de turism - studii și cercetări în turism, 2021)
Tourism contributes to the economy, socio-cultural transmission and adaptation between the people. On an average Assam experience more than 4 million tourists from across the world every year which generates an average revenue of more than Rs. 3.1 million. However the political and the pandemic scenario since October 2019, have left the entire tourism sector devastated which resulted to a loss of more than Rs. 300 crores. Since tourism has a dominant say in the entire economy of the region with innumerable people dependent on it, this paper has been intended to review and understand the prevailing situation of the tourism industry and tried to bring out few measure that can be adopted immediately. On a contrary, the study also throws light on the silver lining of the pandemic, by giving time to the nature to retrieve itself. The study is largely based on primary data collected through sample survey from a cross section of people involved in the tourism sector. The data so gathered have been processed, analyzed and presented using some meaningful statistical and cartographic techniques.